Endoplasmic reticulum stress and exosomes secretion in the pathogenesis of inflammatory bowel disease: a concise summary of research findings - Shibili P, Ashiq; Banerjee, Antara; Chakraborty, Soham; Kondaveeti, Suresh Babu; Porzionato, Andrea; Barbon, Silvia; Pathak, Surajit (Frontiers in Pharmacology, 2025)
Cellular stress responses and intercellular communication play a crucial role in the pathogenesis of Inflammatory bowel disease (IBD). Among these, endoplasmic reticulum (ER) stress and exosome-mediated signaling have emerged as interconnected drivers of chronic intestinal inflammation. Persistent ER stress, primarily through unfolded protein response pathways involving PERK, IRE1, and ATF6, disrupts epithelial barrier integrity, alters immune cell function, and promotes pro-inflammatory gene expression. ER stress not only affects intracellular homeostasis but also modulates intercellular communication through the secretion of exosomes, which carry proteins, lipids, and nucleic acids. This bidirectional relationship ensures that stress-altered exosomes can amplify ER stress and inflammatory signals in neighboring cells, sustaining intestinal inflammation. For this review, relevant research and review articles were retrieved from established search engines and databases, including PubMed, Google Scholar, and ScienceDirect, using key terms such as “endoplasmic reticulum stress,” “exosome secretion,” “exosome cargo,” “inflammatory bowel disease,” “intestinal inflammation,” and “intercellular communication.” The literature search primarily focused on studies published in the last 5 years, prioritizing clinical and preclinical studies (in vivo and in vitro models). Published literature addressing ER stress, exosome biology, and their interconnection in IBD were included, whereas studies lacking relevance or study quality were excluded. Recent findings highlight a dynamic interconnection between ER stress and exosomes, where ER stress modulates exosome biogenesis, secretion, and cargo composition. In contrast, stress-altered exosomes amplify ER stress signals and inflammatory mediators in neighboring cells. This review aims to summarize the current evidences on the interconnection of ER stress and exosomes in modulating the intestinal microenvironment, driving inflammation, and contributing to epithelial and immune dysregulation in IBD. This review also highlights experimental insights, existing challenges, and therapeutic prospects for targeting the ER stress–exosome axis to restore mucosal homeostasis in IBD management.